An Appraisal of the Colombia DDR Process in Light of the Revised Peace Agreement between the Government and the FARC - Capone, Francesca (Estudios en Seguridad y Defensa, 2017)
After more than four years of negotiations the Colombian Government and the FARC have reached a historical peace agreement, signed on 26 September 2016 and, in a shocking turn of events, ultimately rejected in an up-or-down referendum held on 2 October 2016. Only 41 days after the plebiscite the two parties have revised the original deal and submitted a new version to the Congress, which approved it on 30 November 2016. The deal, upon which relies the possibility to finally achieve a stable and lasting peace, covers several crucial issues, including what will happen to the FARC rebels once the armed conflict is officially over. The establishment of an effective DDR process is an essential step to ensure that FARC members will meaningfully transition into civilian life and it represents one of the most controversial aspects of the peace agreement. Moving from the assumption that DDR programmes are not stand alone mechanisms, but fall within a broader framework that covers a number of important and intimately entwined aspects, like the issue of accountability and the rights of victims, the present article, after looking at Colombia’s past attempts to reintegrate former combatants, aims at discussing the DDR process envisaged in the current peace deal, highlighting its main strengths and shortcoming.